Simulasi Numerik Penambahan Slot Per Daun Terhadap Kekuatan Statik Kendaraan Niaga - Muhammad Vendy hermawan; Agung Supriyanto (Fakultas Teknik UMRI, 2020)
Commercial vehicles are a mode of transportation that plays an important role of the nation economy, so it is necessary to pay attention to their effectiveness and efficiency factors. Commercial vehicles have high effectiveness if they are able to send as many goods as possible, but the durability of vehicle components must be considered. One way to increase vehicle load capacity is by adding more slots leaf spring. This study aims to determine the effect of adding slot of leaf spring to the static strength of the rear suspension of Mitsubishi FE 71 110 Ps. This study discusses the static strength of three types of leaf spring arrangement, they are original leaf spring arrangement, the addition of a 700mm spring slot and an additional 1000 mm spring slot. The research was conducted by creating 3-dimensional design drawings and simulating static analysis using SolidWork software. The data sought are the stress and strain values ​​for each variation. The result is the maximum stress value of the original leaf spring arrangement of 14.58 x107 N / m2, an additional slot of 700 mm 21.80 x107 N / m2, and an additional slot of 1,000 mm 24.93 x107 N / m2.